High-Grade Chondrosarcoma of the Proximal Phalanx: an Unusual Case of a Rare Entity - Pagnotta, A; Formica, V M; Taccogna, S; Summa, G; Zoccali, C (Acta chirurgiae orthopaedicae et traumatologiae Cechoslovaca, 2023)
Chondrosarcoma of the hand is a rare disease, but is one of the more common malignancies of the hand. Biopsies and imaging are a fundamental step in determining correct diagnosis, grading and selection for best treatment. We describe the case of a 77-year-old male complaining of a painless swelling in the proximal phalanx of the third ray of left hand. A biopsy was performed and the histology revealed a G2 chondrosarcoma. The patient underwent III ray amputation with metacarpal bone disarticulation and sacrifice of the radial digit nerve of the fourth ray. Definitive histology revealed grade 3 CS. Eighteen months after surgery, the patient is apparently disease-free with a good functional and aesthetic outcome although with persistent paresthesia of the fourth ray. Although there is no agreement in the literature for the treatment of low-grade chondrosarcomas, wide resection or amputation can be considered the mainstay treatment for high-grade tumors. Key words: chondrosarcoma, proximal phalanx, ray amputation, surgical treatment, tumor hand.
Keywords: amputace; Aged; Bone Neoplasms; Bone and Bones; ruka; Humans; Amputation, Surgical; Chondrosarcoma; kosti a kostní tkáň; mužské pohlaví; senioři; lidé; nádory kostí; Male; chondrosarkom; Hand